If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -3x = 7c + -6 Reorder the terms: -4 + -3x = -6 + 7c Solving -4 + -3x = -6 + 7c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -3x = -6 + 4 + 7c Combine like terms: -4 + 4 = 0 0 + -3x = -6 + 4 + 7c -3x = -6 + 4 + 7c Combine like terms: -6 + 4 = -2 -3x = -2 + 7c Divide each side by '-3'. x = 0.6666666667 + -2.333333333c Simplifying x = 0.6666666667 + -2.333333333c
| 8-4r=9+3r | | 3230d-190d=1200+100d | | 36-12a=-21a-9 | | 2240+x(145.50)=4568.00 | | -2=2x^3+6 | | 3=4+x | | -64=8+m | | 2(v-1)+8=6(2x-4) | | -2(-5x-3)-(4-x)=35 | | 21+21m=42+14m | | -46+9x=4x+104 | | 160=-8(1+3x) | | 12s-6/5=6 | | 192x^3+81y^3=0 | | 3.33x-6=-5 | | 8a+a-2=7a+a | | 1+3x+2x=-24 | | 10y+20x=300 | | 380+x(15)=500 | | 3n+4=n+22 | | 3(a-4)=6(a-8) | | -21s=-18.6 | | -99=1-5(3p-1) | | 20x+10y=300 | | -6/15= | | 7(5x-9)=2(6-2x)+x | | -3(w+1)+7w=4(w+1)-5 | | 6x-12=10-2x | | 4x+7x-3=6x+3x+5 | | 2a^2-5a+2=0 | | X(2X-2)+X(7X-3)=(9X+5)(X-1) | | 10a=5(a-3)+15 |